The Association Between Mucin Balls and Corneal Infiltrative Events During Extended Contact Lens Wear - Szczotka-Flynn, Loretta (2011)
PURPOSE: This study determined the association between mucin ball formation and corneal infiltrative events (CIEs) during continuous wear (CW) with lotrafilcon A silicone hydrogel (SH) contact lenses. METHODS: Subjects (n=205) in the Longitudinal Analysis of Silicone Hydrogel Contact Lens Study wore lotrafilcon A contact lenses for 12 months of CW. The primary outcome was a CIE. Kaplan-Meier methods were used to estimate the unadjusted cumulative incidence of remaining CIE free stratified by mucin ball presence. Cox proportional hazards regression was used to model the hazard of developing a CIE as a function of mucin ball formation and other covariates. RESULTS: Over half (54.2%) of subjects displayed some presence of mucin balls during at least one visit and about one-third (32.8%) displayed repeated episodes. Mucin ball scores were correlated between the two eyes and weakly correlated with corneal curvature (p<=0.005). Univariate analyses revealed that the relative hazard for a CIE was 0.35 (95% confidence interval (CI) 0.19–0.68) if a single episode of mucin balls was detected and 0.17 (95% CI 0.06–0.43) if repeated episodes were detected. Upon multivariate analysis, repeated presence of mucin balls was associated with an 84% decreased hazard of experiencing a CIE (hazard ratio 0.16, 95% CI 0.06–0.44). CONCLUSIONS: The presence of mucin balls is significantly associated with a decreased incidence of CIEs, and the effect is greatest when they are repeatedly present over time. We hypothesize that mucin ball presence represents a more concentrated or viscous mucus layer which prevents upregulation of the immune response against bacterial ligands.